Deformations of Integral 1-Form Into Contact-Symplectic Pair - Serigne Abdoul Aziz Dramé; Cheikh Khoule; Ameth Ndiaye (Journal of Mathematics)
The aim of this paper is to give a necessary and sufficient condition of the affine deformation of a contact-symplectic pair via a codimension-one foliation. Some examples are also given.